DEVELOPING WEB-BASED READING COMPREHENSION MODULE FOR UNIVERSITY STUDENTS - Jatmiko, Eko Wahyu (MAGISTRA, 2004)
Around the world, globalization of information access via world-wide-web(WWW) or more popularly known as the internet has revolutionary triggered new method and media of teaching instruction, including language leaching. On the other hand, computer software development has also enchanced the development of Computer Assisten Language Learning (CALL), a new way of language teaching. Over the post decades, reading has been taught traditionally, that is, throught printed passages and questions. It was not until recently that the using. Of interactive computer-based materials modules has been made possible due to the development of present technology. With the benefit of using module, learners con have the autonomy of managing their own learning and adapting their needs of learning to various elements in reading skills and strategies as well as adapting to the level of difficulty. In this paper an example of web-based developed reading module will be displayed This module was developed by lecturers of the English Deportment of Widya Mandala Catholic University Surabaya as a means of teaching activities and also self-study activities for the students.   Key word : web-based, module, CALL